2020
DOI: 10.3390/ijerph17155559
|View full text |Cite
|
Sign up to set email alerts
|

Higher Academic Stress Was Associated with Increased Risk of Overweight and Obesity among College Students in China

Abstract: This study examined associations between academic stress and overweight and obesity, and moderation effects of gender, grade, and types of college on such associations. Data on academic stress, negative learning events, weight, and height were self-reported by 27,343 college students in China in 2018. About 23% and 91% of students perceived high academic stress and suffered from at least one negative learning event during the past six months, respectively, especially for females, undergraduates, and students m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In addition, the outcome expectation can be attached to a greater importance in the Chinese cultural context, which may cause learning motivation problems for medical students and affect their achievement goal orientations ( Liu and Tein, 2005 ). Some studies have shown that the achievement goal orientations of Chinese medical students are more negative than those of general students ( Kim et al, 1997 ; Liu et al, 2000 ; Swetlik and Franco, 2018 ; Chen et al, 2020 ). Therefore, we believe that the level of achievement goal orientations of Chinese medical students is worrying and deserves close attention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the outcome expectation can be attached to a greater importance in the Chinese cultural context, which may cause learning motivation problems for medical students and affect their achievement goal orientations ( Liu and Tein, 2005 ). Some studies have shown that the achievement goal orientations of Chinese medical students are more negative than those of general students ( Kim et al, 1997 ; Liu et al, 2000 ; Swetlik and Franco, 2018 ; Chen et al, 2020 ). Therefore, we believe that the level of achievement goal orientations of Chinese medical students is worrying and deserves close attention.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of overweight and obesity has doubled since 1980 and affects almost a third of the world's population, becoming a public health problem and increasing considerably, especially among university students in developing countries [ 2 ]. In Peru, obesity is a growing problem.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of excess body weight was higher in the last survey than the first survey conducted in 2010. The level of physical activity, eating habits, and stress are factors related to health that can affect body weight maintenance in this public 8,25,27 . In this study, it was possible to note, among the surveys, high prevalence for these characteristics (insufficiently leisure-time physical activity, bad eating habits, and perceived levels of stress), which may clarify these findings regarding the increase in excess body weight.…”
Section: Discussionmentioning
confidence: 99%